1977
DOI: 10.1177/030098587701400208
|View full text |Cite
|
Sign up to set email alerts
|

Ochratoxin A and Citrinin Induced Nephrosis in Beagle Dogs I. Clinical and Clinicopathological Features

Abstract: Ind .A bs t rac t. O chrato xin A a nd cit rinin , bo th m ycot o xins , were give n se para te ly a nd co m bi ne d to yo ung Be agle d ogs for 14 days . O chra tox in A. 0 . 1 a nd 0 .2 mg/ kg , was give n by ca ps u le . a nd citr in in . 5 a nd 10 mg/ kg , was di ssol ved in e tha no l a nd give n by in tr ap erit on e a l inj e cti on . C lin ica l signs o f to xicosis in do gs g ive n 10 mg/k g citrin in a nd th e high er co mb ine d do se s included an o re xia . re tc hi ng . tene smus . wei ght lo ss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
0

Year Published

1977
1977
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 14 publications
2
14
0
Order By: Relevance
“…Several studies conducted in the past on Beagles showed that OTA was lethal in daily doses of 200 g/kg of BW for 2 weeks or in a single dose of 7.8 mg/kg of BW (Szczech et al, 1973). Symptoms such as anorexia, weight loss, vomiting, tenesmus, hemorrhagic diarrhea, dehydration and prostration have also been observed in dogs that had been exposed to this mycotoxin, again for 2 weeks, in doses of between 0.2 and 30 mg/kg of BW (Kitchen et al, 1977).…”
Section: Discussionmentioning
confidence: 97%
“…Several studies conducted in the past on Beagles showed that OTA was lethal in daily doses of 200 g/kg of BW for 2 weeks or in a single dose of 7.8 mg/kg of BW (Szczech et al, 1973). Symptoms such as anorexia, weight loss, vomiting, tenesmus, hemorrhagic diarrhea, dehydration and prostration have also been observed in dogs that had been exposed to this mycotoxin, again for 2 weeks, in doses of between 0.2 and 30 mg/kg of BW (Kitchen et al, 1977).…”
Section: Discussionmentioning
confidence: 97%
“…8 Although citrinin nephrotoxicity might involve the proximal and distal tubule in dogs, 8 citrinin is primarily a proximal tubular intoxicant 9 and has been associated with clinicopathologic evidence of hepatic injury. 7 The authors are not aware of any association of either of these toxins with the presence of unique intrarenal or urinary crystals or uroliths.…”
mentioning
confidence: 97%
“…Dogs given ochratoxin A had necrosis of lymphoid tissues in the spleen, tonsil, thymus, peripheral lymph nodes and lymph nodules of the ileum, colon and rectum. There was ulceration of the mucosa of the intestine in dogs given large combined doses of ochratoxin A and citrinin.The clinical and clinicopathologic features of the mycotoxicoses produced in Beagle dogs by administration of ochratoxin A and citrinin alone and in combination have been described [13]. Pathologic changes induced by ochratoxin A in several species including the rat [19, 20, 23, 24, 27, 281, pig [14][15][16] 251 [22, 271, chick [6, 10, 211 and hen [4] have been described.…”
mentioning
confidence: 99%
“…The clinical and clinicopathologic features of the mycotoxicoses produced in Beagle dogs by administration of ochratoxin A and citrinin alone and in combination have been described [13]. Pathologic changes induced by ochratoxin A in several species including the rat [19, 20, 23, 24, 27, 281, pig [14][15][16]251, rainbow trout [9], dog [26], duckling [22, 271, chick [6,10,211 and hen [4] have been described.…”
mentioning
confidence: 99%